Scripts, Signs, and Swords: The Việt Peoples and the Origin of Nôm - Thompson, Claudia Michele (2000)
Keywords: dept.his

The Hammer of the Inquisitors: Brother Bernard Délicieux and the Struggle Against the Inquisition in Fourteenth-Century France - Friedlander, Alan (Cultures, beliefs, and traditions ; v. 9, 2000)
Keywords: Bernard, Délicieux, frère, approximately 1260-approximately 1320; Franciscans; Biography; Inquisition; Church history; France; Languedoc; Languedoc; Languedoc (France); dept.his; faculty_collection

Historiker als Politiker - Paddock, Troy R. E. (Russen und Russland aus deutscher Sicht: 19./20. Jahrhundert: Von der Bismarckzeit bis zum Ersten Weltkrieg, 2000)
Reprinted in Zauber und Abwehr. Aur Kultutgeschichte der deutsch-russiachen Beziehungen, Dagmar Hermann and Mechthild Keller, eds. (Wilhelm Fink Verlag, 2003)
Keywords: dept.his

Rereading German history: From unification to reunification, 1800-1996 - Paddock, TRE (German Studies Review, 2000)
Keywords: dept.his

A doctor of their own: The history of adolescent medicine. - Metaxas, V (Isis, 2000)
Keywords: dept.his

Eleanor Clarke Slagle and Susan E. Tracy: Personal and professional identity and the development of occupational therapy in progressive era America - Metaxas, VA (Nursing History Review, 2000)
Keywords: *Occupational Therapy/hi [History]; *Professional Autonomy; Female; History, 20th Century; Humans; Job Description; Societies, Scientific/hi [History]; United States; Women's Rights/hi [History]; Women, Working/hi [History]; dept.his

Book Review: The crisis of reason: european thought, 1848–1914: burrow, j. w.: new haven: yale university press, 269 pp., publication date: october 2000 - Paddock, Troy (History: Reviews of New Books, 2000)
Keywords: book.review; dept.his

Book Review: The social history of the third reich, 1933–1945: ayçoberry, pierre: trans. janet lloyd, new york: the new press, 380 pp., publication date: october 1999 - Paddock, Troy (History: Reviews of New Books, 2000)
Keywords: book.review; dept.his